2021
DOI: 10.1002/dvdy.335
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression patterns associated with dental replacement in the rabbit, a new model for the mammalian dental replacement mechanisms

Abstract: Background Unlike many vertebrates with continuous dental replacement, mammals have a maximum of two dental generations. Due to the absence of dental replacement in the laboratory mouse, the mechanisms of the mammalian tooth replacement system are poorly known. In this study, we use the European rabbit as a model for mammalian tooth development and replacement. Results We provide data on some key regulators of tooth development. We detected the presence of SOX2 in both the replacement dental lamina and the rud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This event correlates with the downregulation of canonical WNT signalling in the successional (replacement) dental lamina (i.e. the dental lamina that generates the second tooth set) [ 150 ]. Tooth replacement also requires the specific expression pattern of the following genes: Sox2 in the primary and replacement dental lamina, Sostdc1 (WNT signalling antagonist) between the deciduous tooth germs and the replacement dental lamina, and Runx2 in the tooth mesenchyme [ 149 151 ].…”
Section: Heterochrony Heterotopy and Heterometry In Mammalian Craniof...mentioning
confidence: 99%
See 1 more Smart Citation
“…This event correlates with the downregulation of canonical WNT signalling in the successional (replacement) dental lamina (i.e. the dental lamina that generates the second tooth set) [ 150 ]. Tooth replacement also requires the specific expression pattern of the following genes: Sox2 in the primary and replacement dental lamina, Sostdc1 (WNT signalling antagonist) between the deciduous tooth germs and the replacement dental lamina, and Runx2 in the tooth mesenchyme [ 149 151 ].…”
Section: Heterochrony Heterotopy and Heterometry In Mammalian Craniof...mentioning
confidence: 99%
“…Mice also possess continuously growing incisors (hyperdontia), a capacity linked to the expression of Sox2 in the dental epithelial stem cells located in the cervical loop of the incisors [ 151 , 160 ]. Sox2 -expressing dental stem cells in the cervical loop are also observed in the permanent premolars and molars of the rabbit, which, similar to the mouse incisors, are ever-growing teeth [ 150 ]. On the contrary, in the mouse molars and deciduous premolars and molars of rabbits, which do not constantly grow, Sox2 expression is reduced compared to the ever-growing teeth [ 150 , 151 , 160 ].…”
Section: Heterochrony Heterotopy and Heterometry In Mammalian Craniof...mentioning
confidence: 99%
“…27 During the process of regulating tooth regeneration and replacement, Shh is not expressed in the ferret dental lamina or the mouse RSDL, 28 and Shh signaling does not play a role in successional dental lamina formation. 29,30 A previous report suggested that replacement teeth might inhibit each other's formation. For example, the development of RSDL in mice may be restricted by the relative position and timing of first-generation teeth.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of supernumerary teeth in front of the first molar has been reported in mutant mice based on the down‐regulation of the Shh signaling pathway via the simultaneous deletion of two oral epithelial‐specific enhancers 27 . During the process of regulating tooth regeneration and replacement, Shh is not expressed in the ferret dental lamina or the mouse RSDL, 28 and Shh signaling does not play a role in successional dental lamina formation 29,30 . A previous report suggested that replacement teeth might inhibit each other's formation.…”
Section: Introductionmentioning
confidence: 99%
“…6 The detailed information on Runx2 in the regulation of pathogenicity are summarized in Table 1. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Of interest, some factors could influence the expression of Runx2, which include: (1) microRNAs. The deletion of the micro-RNA processing enzyme Dicer leads to decreased expression of miRNAs and Runx2, which suggests a critical role for microRNA in the regulation of Runx2.…”
mentioning
confidence: 99%